School coexistence based on emotional intelligence, develops soft skills - ALDANA SÁNCHEZ, Jorge Eliécer (2021)
This research establishes a school coexistence program, based on emotional intelligence, to develop soft skills in students of basic secondary education. Supported by a synchronous and asynchronous virtual tool, with parameters proposed by Goleman. Optimizing self-regulation skills, social skills and conflict resolution, to consolidate socially stable environments. Applied or practical research, with an experimental quantitative approach, from a quasiexperimental design, with two intact groups (experimental - control), a Likert scale instrument, subject to content validity and internal reliability. Population made up of 29898 students and an intentional sample, with similarity criteria of 534 students, from four educational institutions. The descriptive statistical analysis, show dynamics of significant changes, the behavior of its variables was estimated with the Shapiro-Willk test, with non-parametric distribution. The hypotheses were contrasted, using the Mann Whitney U test, with effective results: Self-control, Resilience, Leadership, Assertiveness, Teamwork, Empathy, Mediation, Conciliation, checking the alternative hypothesis, after the intervention, all the variables present differences and higher magnitudes, proving that there was significant progress. It is concluded that significant relationships were found between variables and dimensions,confirming that the teaching of soft skills has an impact on school coexistence.Keywords: School coexistence, emotional intelligence, soft skills.